2016
DOI: 10.3390/rs8100858
|View full text |Cite
|
Sign up to set email alerts
|

A Shape-Adjusted Tridimensional Reconstruction of Cultural Heritage Artifacts Using a Miniature Quadrotor

Abstract: Abstract:The innovative automated 3D modeling procedure presented here was used to reconstruct a Cultural Heritage (CH) object by means of an unmanned aerial vehicle. Using a motion capture system, a small low-cost quadrotor equipped with a miniature low-resolution Raspberry Pi camera module was accurately controlled in the closed loop mode and made to follow a trajectory around the artifact. A two-stage process ensured the accuracy of the 3D reconstruction process. The images taken during the first circular t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Remote sensing data with ultra-high spatial resolution (e.g. centimeter-level) plays significant roles in some fine-scale remote sensing applications, such as railway monitoring, dam/bridge crack detection, reconstruction and restoration of cultural heritage [9]. Besides, numerous studies have reported that images with centimeter-level spatial resolution (up to 5 cm or more) hold the potential for studying spatio-temporal dynamics of individual organisms [10], mapping fine-scale vegetation species and their spatial patterns [11], estimating landscape metrics for ecosystem [12], monitoring small changes of coasts by erosion [13], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Remote sensing data with ultra-high spatial resolution (e.g. centimeter-level) plays significant roles in some fine-scale remote sensing applications, such as railway monitoring, dam/bridge crack detection, reconstruction and restoration of cultural heritage [9]. Besides, numerous studies have reported that images with centimeter-level spatial resolution (up to 5 cm or more) hold the potential for studying spatio-temporal dynamics of individual organisms [10], mapping fine-scale vegetation species and their spatial patterns [11], estimating landscape metrics for ecosystem [12], monitoring small changes of coasts by erosion [13], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Despite photogrammetry being an old discipline, used for purposes other than 3D reconstruction, some studies (Covas et al;Louiset et al;2016;Utomo and Wibowo;2017) that fall under this category present interesting advances. For example, Covas et al (Covas et al; used sh-eye images to reconstruct hard-to-reach parts of two medieval castles in Portugal.…”
Section: Image-basedmentioning
confidence: 99%
“…Conversely, Louiset et al (Louiset et al;2016) devised a reconstruction method using a miniature unmanned aerial autonomously ying in close proximity of the reconstructed object. In this approach, the vehicle ies twice around the object once in a circular trajectory and a second time with a trajectory that approximates the shape of the object, with the results of the second ight being used to improve the realism of the initial reconstruction.…”
Section: Image-basedmentioning
confidence: 99%
“…Recently, a lightweight sensor composed of four stereo heads and an inertial measurement unit (IMU) were developed to perform FPGA-based dense reconstruction for obstacle detection in all directions at 7 Hz output refresh rate [136]. In another application, a drone of a mass less than 500 g was developed for photogrammetric 3D reconstruction applied to a cultural heritage object [137] but requiring a motion capture system to determine accurately their pose of the robot at a frequency of 500 Hz. Better understanding how flying insects work will therefore help future drones to operate inside buildings where obstacles are very close.…”
Section: Drones In the Field Of Architecturementioning
confidence: 99%